Extensibility Interaction Flow Modeling Language Metamodels to Develop New Web Application Concerns - Wakil, Karzan; Jawawi, Dayang N.A. (Kurdistan Journal of Applied Research, 2017)
Web engineering is a systematic approach to develop web applications, and numerous web engineering methods have been proposed. These methods were extended through defining new models by using different mechanisms to capture the web application concepts. Due to the complexity rising of web applications, the web engineering methods cannot provide web solutions anymore. Even though Interaction Flow Modeling Language (IFML) is recently proposed as a new method for developing web applications, it has limitations. Therefore these methods need to be improved. In this paper, we present the ability of IFML extensibility to support new concerns from web applications. Moreover, we extend IFML through UML mechanisms to support new concerns from the context to the user interface. The new IFML solves the lack of context web application through defining a new model and becomes a new direction to develop concerns modern web applications.